ZAKAT AS SOCIAL FUNCTION OF SHARIAH BANKING RELATED TO SMEs EMPOWERMENT FORPOVERTY ALLEVIATION - Mispiyanti, Mispiyanti; Junaidi, Junaidi (UNISSULA, 2016)
Corporate Social Responsibility(CSR) is no longer a voluntary action. It already has became an obligation.Moreover, for syaria monetary institution which bases it principals on, not only morality and ethics, but also religion and spirituality. The object of this research are: BMI bank of Indonesia, BIMB bank of Malaysia, ADIB bank of UEA, and Al Baraka bank of Bahraen. It based its data on 2013 –2014 annual report. The research uses content analysis to analyze the bank’s zakatand itsrelationto the degree of poverty alleviation. The results are: 1) BMI and BIMB banks did their social function in terms of people basic needs, while 2) ADIB and Al Baraka banks also did their role, in terms of recognition development and human resources development. Implementation of CSR for each bank and the state can be different according to the conditions, needand problems which faced by their people. CSR implementation could be relative because each state has a different focus, it could be some required activities for BMI and BIMB